The Rapeseed Potential in Poland and Germany in the Context of Production, Legislation, and Intellectual Property Rights - Woźniak, Ewa; Waszkowska, Ewa; Zimny, Tomasz; Sowa, Sławomir; Twardowski, Tomasz (Frontiers in Plant Science, 2019)
Rapeseed is an essential crop which used in many different areas as edible oil, biodiesel, lubricant and feed. It is one of the most popular oil crops in Europe (63% of oilseeds production in 2017). The current study highlight the potential for further rapeseed development in European Union (EU) was examined, with special emphasis on Germany (19% of EU production) and Poland (12% of EU production). The study focused on three factors: cultivation area, volume of production and the numbers of Intellectual Property Rights (IPR), in particular patents granted for rapeseed or rapeseed related inventions and plant variety rights. Possible further obstacles to development, such as current legal framework were also taken under consideration. The analyzed statistical data shows that both the cultivation area, as well as the volume of production of rapeseed fluctuated in the last decade in both examined countries, while the numbers for European patent publications and Community Plant Variety Rights showed a rising trend, indicating investments in the Research and Development (R&D) of the crop. The data analysis seems to confirm a hypothesis that there is a potential for the development of rapeseed as a versatile, multi-use crop, however the current EU GMO policies and a legal uncertainty as to the status of products of certain modern genome editing techniques may hamper making optimal use of this potential.